Intervention effect of psychodrama on depression and anxiety: A meta-analysis based on Chinese samples. (July 2020) - Wang, Qi; Ding, Fan; Chen, Danni; Zhang, Xinyu; Shen, Kehan; Fan, Youyuan; Li, Ling
Highlights: Psychodrama is effective for Chinese participants suffering from depression and anxiety. Psychodrama is more effective for those with undiagnosed anxious and/or depressive emotions than those clinically diagnosed and hospitalized. Classical psychodrama is more effective than scene psychodrama, a new well-known form of psychodrama in China. Abstract: In this meta-analytical study, we investigated the effectiveness of psychodrama as a treatment for depression and anxiety in Chinese participants. Although documents verifying the effects of psychodrama are rich in western countries, the studies on the effects of psychodrama in Chinese samples are rare, partly because psychodrama has been newly introduced. Considering the differences between Chinese and Western culture, it is necessary to examine the effectiveness of psychodrama applied in Chinese participants. This study analyzed experimental studies that investigated the effectiveness of psychodrama ( N = 9) with regard to depression and anxiety. Sub-group analyses were conducted to compare different kinds of participants (clinical and non-clinical) and different types of psychodrama (classical and scene). Results suggest that psychodrama significantly mitigates the symptoms of depression and anxiety in Chinese participants, which concurs with findings from studies in Western culture. The findings also suggest that in the Chinese cultural setting, Psychodrama is more effective for the participants who have some anxious and/or depressive emotions but without clinical diagnoses than for those clinical diagnosed and hospitalized clients. Moreover, we found that classical psychodrama is more effective for Chinese participants compared with scene psychodrama, a new well-known form of psychodrama in China. Future research possibilities and application of psychodrama in the Chinese cultural context are discussed.